Direct synthesis of nanorod stacked "nest-like" hierarchical ZSM-48 hollow spheres using a triazine-based bolaform organic structure-directing agent. Issue 9 (22nd March 2022) - Wang, Risheng; Peng, Zhihua; Wu, Pingping; Sun, Hongman; Zhang, Yu; Subhan, Fazle; Yin, Hailiang; Wang, Youhe; Yan, Zifeng
Abstract : Ordered "nest-like" hierarchical ZSM-48 (NSH-ZSM-48) hollow spheres stacked by uniform nanorods with superior accessibility were synthesized utilizing a novel bolaform s-triazine based surfactant, and the proper formation mechanism was proposed. Abstract : Rational design of organic structure-directing agents (OSDAs) is always regarded as a promising strategy to produce ZSM-48 with diverse configurations. However, to date, only OSDAs with alkyl and alkenyl groups have been employed to produce *MRE zeolites with different structures. Aromatic heterocyclic groups were rarely considered for the synthesis of ZSM-48 with a unique nanostructure. In this work, a triazine-based bolaform quaternary ammonium bifunctional template was designed for the first time to fabricate nanorod stacked hierarchical ZSM-48 (NSH-ZSM-48). Nanorod-stacked ZSM-48 with different SiO2 /Al2 O3 ratios ranging from 100 to 500 was obtained via a conventional procedure, using the synthesized s-triazine based OSDA, and a reasonable formation mechanism was proposed based on geometrical matching. We also demonstrated that the ZSM-48 nanorods piled up to form an ordered bird's nest-like hollow sphere configuration. The synthesized NSH-ZSM-48 possesses abundant mesopores and a high surface area, attributed to the SDA's mesopore-forming and nanonrod's stacking abilities. In contrast to conventional materials, 1 wt% Pd/NSH-ZSM-48 experiences a dramatic increase in the conversion (3.59%) and selectivity (95.7%) of a cyclohexanol/cyclohexanone mixture in the selective oxidation of cyclohexane, which are higher than those for silicalite-1 and SBA-15 with the same loading (2.11%/66.1% and 1.76%/68.5%, respectively).